Synthesis and Characterization of Reduced Graphene Oxide (rGO)/Polyaniline (PANI) Composite as a Solid Electrolyte in Batteries - Karisma, Siska; Yuningsih, Lela Mukmilah (Fakultas Teknik, Universitas Lampung, 2025)
rGO is a graphene derivative that has undergone reduction of its oxygen groups. Synthesis and characterization of rGO/Polyaniline composite as a solid electrolyte in batteries to analyze the ability to store electric current and voltage. rGO was synthesized by the modified Hummers method and reduced with Zn reductant. Graphite oxide was first synthesized by oxidizing graphite using H2SO4 and KMnO4. Graphite oxide was exfoliated ultrasonically at 50/60 Hz wave beam and treated with Zn to produce rGO in powder form. Polyaniline (PANI) was synthesized using the in-situ polymerization method. rGO and PANI were composited with the aim of increasing their conductivity values ​​so that there was an increase in their current and voltage values. The rGO/PANI composite was characterized using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), Raman spectroscopy, LCR-Meter, and digital multimeter. In FTIR, absorption peaks identified as rGO appear at wave numbers 1643 cm-1 (C=O), 1483.26 cm-1 (C-H stretch), 1292 and 1238 cm-1 (C-O stretch). While the typical PANI bands appear at wave numbers 684 cm-1 and 785 cm-1 (C-H bending), 1568 cm-1 (C=C stretch), and 3460.65 cm-1 (N-H). The resulting ID/IG ratio in Raman spectroscopy is 0.83. The rGO/PANI composite is identified to have a conductivity value of 0.230739696 S/cm, a voltage of 1.17 V with a current of 3.22 mA. The obtained values ​​are higher than the results of rGO measurements described singly.